Adjustable Male Sling: Our Experiences with Placement of Adjustable Male Sling, Including a Case of Exstrophy-Epispadias: Initial Report - Basiri, Abbas; Kilani, Hossein (Urology Journal, 2013)
PURPOSE: To present our experience of using an adjustable male sling, Argus® (Promedone SA; Cordoba, Argentina), in patients with stress urinary incontinence (SUI), and report its success, extension of indications, and management of complications. MATERIALS AND METHODS: We retrospectively evaluated Argus implantation results in 17 patients, including 15 post prostatectomy incontinence, one exstrophy-epispadias, and one neurogenic bladder patient. Of 17 patients, 12 had severe (more than 5 pads daily) and 5 had moderate SUI (2 to 5 pads daily). Seven patients had history of previous surgeries. Patients were evaluated pre-operatively with urodynamic study and cystoscopy. RESULTS: After median follow-up of 11.8 months (range, 3 to 22 months), 9 patients were continent, 7 had mild SUI (1 pad daily), and one had the device removed due to perineal and bladder symptoms. Argus adjustment was done in 10 out of 17 patients; 8 tightening and 2 loosening. In a totally incontinent exstrophy-epispadias patient with a history of multiple bladder surgeries, continence was achieved after device readjustment. In a patient with neurogenic bladder with a history of cystoplasty, severe SUI changed into a moderate sporadic SUI. In 2 patients, prosthesis infection occurred, which was managed with antibiotics without the need for Argus explantation. CONCLUSION: Argus is a simple and good device to control incontinence in men. It may also be used in exstrophy-epispadias patient who is not a candidate for urinary sphincter implantation. Infection complication may be managed conservatively. To the best of our knowledge, this is the first report of successful Argus implantation in exstrophy-epispadias patient.